2020
DOI: 10.1108/par-04-2020-0049
|View full text |Cite
|
Sign up to set email alerts
|

Female board directorship and earnings management

Abstract: Purpose This paper aims to examine the impact of female board directorship on the extent of earnings management. Design/methodology/approach The research hypotheses have been tested using both univariate and multivariate analyzes based on a sample of 198 firm-year observations from closely-held family firms listed on the SBF 120 over the period 2010–2018. Findings The empirical results first indicate that female board participation reduces the level of earnings management. When looking at women positions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 83 publications
3
45
0
10
Order By: Relevance
“…These findings are explained by the idea that the increase of leverage may motivate the management to engage in earnings management practices to alleviate the negative impact of debt on the financial statements. However, Mnif and Cherif (2020) found no association between firm leverage and earnings management. Following prior studies, the current study suggests that earnings management in UAE is negatively associated with firm leverage.…”
Section: Firm Leverage Levementioning
confidence: 87%
See 2 more Smart Citations
“…These findings are explained by the idea that the increase of leverage may motivate the management to engage in earnings management practices to alleviate the negative impact of debt on the financial statements. However, Mnif and Cherif (2020) found no association between firm leverage and earnings management. Following prior studies, the current study suggests that earnings management in UAE is negatively associated with firm leverage.…”
Section: Firm Leverage Levementioning
confidence: 87%
“…El Guindy and Basuony (2018) found a negative relationship between firm size and earnings management. Moreover, in Tunisia, Mnif and Cherif (2020) revealed that earnings management is negatively associated with firm size. They argued that large firms are monitored by the government, which reduces the misbehaviour of the management.…”
Section: Firm Leverage Levementioning
confidence: 99%
See 1 more Smart Citation
“…In what follows, we will focus on board gender diversity as a possible control mechanism that underlies the relationship between CSR and REM. Several previous works concluded that the board gender diversity might constitute a mechanism that inhibits discretionary behaviours (Lakhal, Aguir, Lakhal, & Malek, 2015;Triki Damak, 2018;Orazalin, 2019;Mnif & Cherif, 2020). Thus, board gender diversity could moderate the expected negative relationship between CSR and REM.…”
Section: The Moderating Role Of Board Gender Diversity On the Relatio...mentioning
confidence: 94%
“…Regarding this, female directors influence changing norms on the board (Yang et al, 2019). Some studies conducted (Luo et al, 2017) on the association of manipulation activities, earning management (Gull et al, 2018), (Zalata et al, 2019), (Harakeh et al, 2019), (Arioglu, 2020), (Ammer & Ahmad-Zaluki, 2017), (Mnif & Cherif, 2020), and financial irregularities (Li & Li, 2020). (Li & Li, 2020) Female chairperson Committee audit…”
Section: B Earnings Management and Financial Manipulationmentioning
confidence: 99%